First report of tamoxifen‐induced baboon syndrome. (13th December 2020) - Mofarrah, Ramin; Mofarrah, Ramina; Kränke, Birger; Rahmani, Maziar; Jahani Amiri, Kousar; Ghasemi, Maryam; Jallab, Naghmeh; Ghobadiaski, Sueshianth; Rahmani, Nazgol; Hashemi, Narges
Abstract: Background: Baboon syndrome is a rare, type IV hypersensitivity reaction causing a maculopapular rash. Tamoxifen is an antineoplastic agent, working as an estrogen receptor antagonist, also called a selective estrogen receptor modulator. A variety of rashes were reported with Tamoxifen use to‐date except baboon syndrome. The Tamoxifen‐induced baboon syndrome seems to be reversible, as discontinuation of the drug improves clinical outcomes. Aim: Herein, we present the first case of Tamoxifen‐induced baboon syndrome which occurred 8 years after initiation of Tamoxifen use. Patients: A 44‐year‐old woman presented with papulovesicular eruption on her body and erythema on her face for a duration of 6 months. There was no evidence of ocular or mucosal involvement. She was diagnosed with breast cancer and treated with tamoxifen 10 mg twice daily over the past 8 years. She was not taking other medications or over‐the‐counter supplements at the time of presentation. The patient underwent urgent skin biopsies of two lesions on her buttock and thigh. No organisms were seen on Gram stain. The patient's skin biopsy revealed extensive hyperorthokeratosis, minimal parakeratosis, hypergranulosis, and lichenoid interface dermatitis in the irregularly acanthotic epidermis supporting diagnosis of fixed drug eruption. Following a multidisciplinary discussion, the patient was diagnosed with baboon syndrome or symmetrical drug‐related intertriginous and flexural exanthema (SDRIFE) associated with Tamoxifen. Results: Hence, Tamoxifen was immediately discontinued and treated with oral steroid along with topical agents. She showed improvement of clinical abnormalities within days after discontinuation of Tamoxifen. Conclusions: Given the widespread use of Tamoxifen in the management of patients with breast cancer, it is important that healthcare professionals monitor for rare, however clinically significant, and potentially life‐threatening dermatological manifestations of Tamoxifen use, such as baboon syndrome.